2014
DOI: 10.1111/jlme.12189
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Education: A Theoretical Orientation Incorporating Profession-Centrism and Social Identity Theory

Abstract: To improve health for our citizens our health work force must be team focused and collaboration ready. The theory of social identity is used to explain profession-centrism and ultimately inform our understanding of the challenges of developing and implementing interprofessional education curricula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 8 publications
0
42
0
Order By: Relevance
“…Students enter post-secondary education, even at the freshman level, with these preconceived ideas of different healthcare professions (Reeves, 2000;TunstallPedoe et al, 2003). These professional values begin to be internalized as soon as students begin their post-secondary education career, contributing to the challenges of interprofessional education and breaking down the disciplinary silos (Cooke et al, 2003;Cooper et al, 2005;Pecukonis, 2014;Tunstall-Pedoe et al, 2003). According to student responses, Cooke et al (2003) found that the stereotypical hierarchy did not have a negative effect when different groups of students worked together.…”
Section: Professional Stereotypesmentioning
confidence: 99%
See 4 more Smart Citations
“…Students enter post-secondary education, even at the freshman level, with these preconceived ideas of different healthcare professions (Reeves, 2000;TunstallPedoe et al, 2003). These professional values begin to be internalized as soon as students begin their post-secondary education career, contributing to the challenges of interprofessional education and breaking down the disciplinary silos (Cooke et al, 2003;Cooper et al, 2005;Pecukonis, 2014;Tunstall-Pedoe et al, 2003). According to student responses, Cooke et al (2003) found that the stereotypical hierarchy did not have a negative effect when different groups of students worked together.…”
Section: Professional Stereotypesmentioning
confidence: 99%
“…Working collaboratively can be time-consuming and heavy workloads can be a barrier (Hepp et al, 2015). Although these concerns are indeed challenging, perhaps the biggest threat to the implementation and success of interprofessional education and collaborative practice are the longstanding professional stereotypes and ingrained professional cultures (Barton, 2009;Pecukonis, 2014).…”
Section: Challenges To Implementation Of Interprofessional Education mentioning
confidence: 99%
See 3 more Smart Citations